Phenotypic Diversity in Caucasian Adults with Moderate to Severe Class II Malocclusion - Moreno Uribe, Lina M. (2014)
INTRODUCTION: Class II malocclusion affects about 15 % of the US population and is characterized by a convex profile and occlusion disharmonies. The specific etiological mechanisms resulting in the range of Class II dento-skeletal combinations observed is not yet understood. Most studies describing the class II phenotypic diversity have utilized moderate sample sizes or have focused on younger individuals that later in life may outgrow their class II discrepancies; such a focus may also preclude the visualization of adult class II features. The majority have utilized simple correlation methods resulting in phenotypes that may not be generalizable to different samples and thus may not be suitable for studies of malocclusion etiology. The purpose of this study is to address these knowledge gaps by capturing the maximum phenotypic variation present in a large Caucasian sample of class II individuals selected with strict eligibility criteria and rigorously standardized multivariate reduction analyses. METHODS: Sixty-three lateral cephalometric variables were measured from pre-treatment records of 309 Class II Caucasian adults (82 males, 227 females; ages 16–60 years). Principal component analysis (PCA) and cluster analysis were used to generate comprehensive phenotypes in an effort to identify the most homogeneous groups of individuals reducing heterogeneity and improving the power of future malocclusion etiology studies. RESULTS: PCA resulted in 7 principal components that accounted for 81% of the variation. The first three components represented variation on mandibular rotation, upper incisor angulation and mandibular length, respectively. The cluster analysis identified 5 distinct Class II phenotypes. CONCLUSIONS: A comprehensive spectrum of Class II phenotypic definitions was obtained that could be generalized to other samples advancing our efforts to the identification of etiological factors underlying Class II malocclusion.